A Content-Centric Development Process Model. - Moreno-Ger, Pablo; Martíne-Ortiz, Iván; Sierra, Joé Luis; Fernández-Manjón, Baltasar (Computer (00189162), 2008)
The article discusses the need for a well-defined development process model for educational games development that seamlessly includes game writers and instructors in a traditional game development organization. According to the authors, they advocate a development process model in which the game writers know precisely what can and can not be don with the current language because they are the final users of the language. The application of the documental approach to educational game development is also described.